A ferrocene based glucose biosensor with an extended linear measuring range - Jusoh, Norhana (2009)
The work described in this research is centred on the performance of ferrocene as a mediator to replace oxygen in the oxidation of glucose. Three immobilization methods were studied to minimize the leaking of the mediator. Glucose oxidase (GOD) and ferrocene mediator were immobilized in cross-linked poly(vinyl alcohol) (CLPVA), composite sol-gel-silica (SGS)/CLPVA/nafion and layer-by-layer (multilayer) covalent attachment. The biosensor response was evaluated amperometrically at 0.363V (vs. Ag/AgCl). The results showed that SGS/CLPVA/nafion membrane demonstrated the highest ability in retaining the enzyme and mediator whilst CLPVA membranes showed the poorest ability. The low current response with high Michaelis-Menten constant (Km app) and slow response time was observed in CLPVA membrane. Relative to that, SGS/CLPVA/nafion membrane and multilayered membrane were able to achieve larger current responses with lower Km app at faster response time. CLPVA was able to retain only 10% of the initial current whilst SGS/CLPVA/nafion and multilayered membranes were able to retain about 83% and 76% respectively of the initial current after 2 months of storage. All membranes showed good sensitivity with good stability except the CLPVA membranes. The Km app value for multilayered membrane was increased up to 28.68mM after the addition of nafion to the membrane. With such a high Km app, multilayered-nafion membrane can be applied as the enzymatic layer for a glucose biosensor since the value nearly encompasses the relevant concentration of glucose in blood which is from 1mM to 30mM. Subsequently, three types of external membranes were attached to the multilayered-nafion membranes to extend the linearity of sensor response and also to protect the biosensor. The external layers were cross-linked poly(2-hydroxyethyl methacrylate) (pHEMA), cellulose acetate incorporated poly(2-hydroxyethyl methacrylate) (CA-pHEMA) and cellulose acetate incorporated poly(ethylene glycol) (CA-PEG). Among these three types outer membranes, multilayered-nafion membranes with cross-linked pHEMA demonstrated acceptable Km app, which was around 40.58mM with high sensitivity and fast response time towards the glucose. Overall, the ferrocene based glucose biosensor showed very promising performances.